Upaya Meningkatkan Kemampuan Passing Bawah Bola Voli Melalui Media Dinding Sekolah Dengan Metode Drill Pada Siswa Kelas IV SD Negeri Mayana 01 - Herlan Nurdiansyah; Dedi Iskandar (Harmoni Pendidikan : Jurnal Ilmu Pendidikan, 2025)
This research aims to improve students’ bottom passing skills using school wall media using the Drill method. This research is Classroom Action Research which was carried out in 2 cycles. The research was carried out in April of the 2024/2025 academc year. Researchers collaborate with teachers and colleagues. This research procedure refers to the Kemmis dan Mc model. Taggart which includes planning, implementing actions, observing and refleting. The research subjects were fourth grade students at  SD Negeri Mayana 01, totaling 20 students. 9 male students and 11 female students. The instruments used are teacher activity observation assessment sheets, students activity observation sheets, and performance assessment sheets. The results of the research showed that there was and increase in cooperation in the firts cycle, namely students’ bottom passing skills using school wall media. Of the 20 students at meeting 1, there were 10 students  ( 50% ) who had antered the criteria. For completion, while at meeting 2 there were 12 students ( 60% )  who had entered, in the complete criteria. In cycle II, students’ underpassing skills used school wall media. Of the 20 students at meeting 1, 15 students   ( 75% ) had entered the completion criteria, while at meeting 2 there were 18 students  ( 90% ) had enteered the completion creteria. Based on these data, it can be concluded that the use of the Drill method wits school walls can improve students’ bottom passing skills in cless IV of SD Negeri Mayana 01, , Bantarkawung District, Brebes Regency.